Analysis of Land Tax in The Plantation Sector Viewed from Islamic Economic Leaders - Batubara, Sarmiana; Yuslem, Nawir; Yafiz, Muhammad (UPT Publikasi Ilmiah UNISBA, 2024)
This research is concerned with how land and building taxes affect the plantation sector in Indonesia by following one of the economic thought leaders Abu Yusuf in achieving justice. The researchers applied literature research or content analysis. Land and Building Tax for the Plantation Sector in Indonesia is seen from the point of view of Abu Yusuf because the idea will create justice for taxpayers, even though the tax must be paid 0.5% based on the Sales Value of the Tax Object (NJOP). The muqasamah system presented by Abu Yusuf pays more attention to details, starting from the type of land, soil fertility, irrigation, seasons, and price fluctuations at harvest, to ensure fairness in tax collection. If the muqasamah system is implemented in Indonesia, which has the character of an agrarian country, then state revenue from the plantation sector tax will have great potential. The concept put forward by Abu Yusuf is still very relevant to Indonesia, particularly in land and building taxes in the plantation sector. Therefore, the concept of Abu Yusuf can be considered by the Indonesian government in establishing policies related to land and building taxes in the plantation sector nationally